TRADISI SYAWALAN di Morodemak, Bonang, Demak - Khoirul Anwar (Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
This paper describes the tradition of Syawalan at Morodemak Village, District Bonang, Demak regency to reveal the meaning of the tradition for the community. Direct observations, interviews and examination of secondary data, explain that the tradition for the people of Morodemak, is a form of gratitude to the Almighty God for the gift of the abundance of seafood as well phrase prayer of salvation from all dangers that can arise from the sea. Tradition also has significance of Syawalan concern for nature, especially the sea as well as the meaning of cohesion and communality among fishing communities. In addition to these cultural meanings, tradition of Syawalan also has economic and socio-cultural significance for local government and communities.